The General Review on How Outsourced Marketing Improves the Productivity of a Company (Global Journal of Management and Business Research, 2015)
Outsourcing is becoming a common topic now as many companies choose to outsource functions so they can improve the productivity of the company. The objective of this article primary discuss about outsourcing, particularly outsourced marketing and how it improves the productivity of a company. Outsourcing is the practice of having certain job functions done outside a company instead of having an in-house department or employee handle them. Thus, a company benefits from outsourcing by taking advantage of specific expertise, marketing in this case, without having to hire professional marketers or train inexperience ones which can be costly. Different organizations go for different kinds of outsourcing, based on the company's weaknesses and strengths identified, but it is the usually non-core aspects of the business that are outsourced. The relationships between the outsourced company and the providers can directly affect the productivity of the company. Many companies view outsourcing as one of the ways for a large company to expand its capacity without incurring significant entry and overhead costs. Despite the common view that outsourcing is reserved only for large companies due to its huge cost, in the last 10 years outsourcing has also become affordable for small companies. At the end of the article, we will manage to have a clear vision of the potential of outsourcing, why it is a trends in the modernization of marketing operations and the benefit of using the power of outsourcing.
Keywords: outsourcing; outsourced functions; outsource marketing; productivity; non-core functions; efficiency; benefit of outsourcing